Divergent Interpretations and Inter-Organizational Relations of Halal Product Guarantee Policy in Indonesia - Agus Iswanto; Koeswinarno Koeswinarno (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2020)
The emergence of the issue of halal products, both in the form of food and services, has also led to competition regarding the certification of halal products. Studies on competition between certification bodies have been carried out, but these studies do not focus on the competition that occurs in Southeast Asian countries, including Indonesia which is a big market for the halal industry. In Indonesia, the implementation of the regulation of Halal Product Guarantee (HPG) in Law No. 33 2014 still raises problems, including the related issue of inter-organizational relations. This article discusses the relations between organizations based on the interpretation of each party related to the Halal Product Guarantee policy, and the consequences arising from it. This article used new institutional theory, and a semiotics approach as analysis of verbal signs and gestures raised by each of the parties. This article argued that the interpretations of each organizational actor towards the new halal certification policy in Indonesia are driven by different institutional reasons/logics, resulting in contradictions, even conflicts related to the relationship between organizations implementing the policy. The difference in meaning, especially in the connotative meaning, shows the difference in institutional logic. Thus, there is a divergence in meaning. Therefore, it is important to equate significance (meaning/interpretation) to each of the institutions related to Halal Product Guarantee in order to realize the implementation of the regulations properly.